Teratai (Nelumbo nucifera Gaertn.): Botani, Potensi Pemanfaatan, dan Metabolit Sekunder - Marina Silalahi; Sri Mulyaningsih; Linggom Kurniaty (Pro-Life, 2025)
Nelumbo nucifera Gaertn is one of the aquatic plants used for food, medicine, culture, and religion. This study aims to explain the botany, utilization, bioactivity, and secondary metabolites of N. nucifera. This study is based on a literature review published online using the keywords N. nucifera, uses of N. nucifera, and bioactivity of N. nucifera. Data analysis was carried out qualitatively to describe the botany, utilization, and secondary metabolites of N. nucifera. In taxonomy, N. nucifera is grouped in the Nelumbonaceae family. N. nucifera is a perennial aquatic plant with a rhizome stem and a single, round leaf with large pink or white flower petals. In traditional medicine, N. nucifera is used to treat various diseases such as inflammation, insomnia, cardiovascular issues, hyperlipidemia, nervous disorders, emollient and diuretic effects, diarrhoea, dyspepsia, hematuria, fever, epilepsy, hypertension, and obesity. N. nucifera bioactivity as an antioxidant, anti-cancer/tumor, neuroprotective, anti-inflammatory, increases sperm motility, anti-diabetes mellitus, and skin whitener. Lotus has flowers, seeds, leaves, fruits, and rhizomes that can be eaten because they have more carbohydrates, proteins, and vitamins. Alkaloids, polyphenols, terpenoids, steroids, and glycosides are responsible for its various biological and pharmacological activities. The potential for utilizing N. nucifera for food diversification, vegetable protein sources, and skin whitening needs to be studied further.